Aitareyopaniṣat : Ānandagirikrtaṭīkāsaṃvalitaśaṅkarabhāṣyasametā taṭhā ca Vidyāraṇyaviracitā Aitareyopaniṣaddīpikā - Ānandagiri, 13th cent; Śaṅkarācārya; Mādhava, 1386 (SAMP early 20th-century Indian books project ;, 1911)
Hindu philosophical classic with commentary of Ānandagiri, Śaṅkarācārya and Mādhava, d. 1386.